5x-23=10x-47

Simple and best practice solution for 5x-23=10x-47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-23=10x-47 equation:


Simplifying
5x + -23 = 10x + -47

Reorder the terms:
-23 + 5x = 10x + -47

Reorder the terms:
-23 + 5x = -47 + 10x

Solving
-23 + 5x = -47 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-23 + 5x + -10x = -47 + 10x + -10x

Combine like terms: 5x + -10x = -5x
-23 + -5x = -47 + 10x + -10x

Combine like terms: 10x + -10x = 0
-23 + -5x = -47 + 0
-23 + -5x = -47

Add '23' to each side of the equation.
-23 + 23 + -5x = -47 + 23

Combine like terms: -23 + 23 = 0
0 + -5x = -47 + 23
-5x = -47 + 23

Combine like terms: -47 + 23 = -24
-5x = -24

Divide each side by '-5'.
x = 4.8

Simplifying
x = 4.8

See similar equations:

| 1+4n=-13+5n-8n | | 8x=12+x^2 | | 5x+(x-2)+3(x-4)=1 | | 17.5-(42.2)= | | -m^2+14-16m^2+13+m^2= | | (4x-5)(6x+5)= | | 108=-5x+3 | | x-2(x+3)+4(x-1)=2 | | x-2(x+3)+4(x-1)=22 | | -5(3x-5)=-15x+25 | | 2x(x+3y+4z)= | | 11*1.86-12= | | X^2+1x+.25=0 | | -31-9x=-6x+32 | | y-x^2+6x=k | | 5x-10+(-9)=-7+7x | | 8x+11=3x-19 | | -14b-5=12b+8 | | -20-6x=6-4x | | 4x+4(x-1)+2(x-3)=0 | | 21=-27+6x | | -3(9+a)=33 | | 8+11a=-234 | | B(3b-1)= | | 13m-7-10(3m+10)= | | 12x-118=138-4x | | -5(3x-9)+7=-15x+52 | | 6x+10=5(-2x+-4) | | 144+2x=64+22x | | 11111111111111116=5x | | 144+2x=64+22 | | -159-5x=12x+96 |

Equations solver categories